2016
DOI: 10.1161/strokeaha.116.012890
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized Infection as a Trigger for Acute Ischemic Stroke

Abstract: Background and Purpose Acute triggers for ischemic stroke, which may include infection, are understudied, as is whether background cardiovascular disease (CVD) risk modifies such triggering. We hypothesized that infection increases acute stroke risk, especially among those with low CVD risk. Methods Hospitalized strokes and infections were identified in the Atherosclerosis Risk in Communities (ARIC) cohort. A case-crossover design and conditional logistic regression were used to compare hospitalized infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…A composite measure of chronic infection assessed by serologies against several common bacterial and viral infections was associated with increased long‐term stroke risk in the Northern Manhattan Study 6. In case‐crossover analyses from both the Cardiovascular Health Study and the Atherosclerosis Risk in Cardiovascular Disease Study, recent hospitalization for infection was associated with increased risk of stroke 7, 8. The association between infection and stroke diminishes over time, however.…”
Section: Introductionmentioning
confidence: 99%
“…A composite measure of chronic infection assessed by serologies against several common bacterial and viral infections was associated with increased long‐term stroke risk in the Northern Manhattan Study 6. In case‐crossover analyses from both the Cardiovascular Health Study and the Atherosclerosis Risk in Cardiovascular Disease Study, recent hospitalization for infection was associated with increased risk of stroke 7, 8. The association between infection and stroke diminishes over time, however.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other research on infection and CVD has found that infection is a stronger CVD risk factor among those with low background CVD risk compared to those with elevated background CVD risk. 24 It is possible EI was a risk factor for CVD among ARIC participants when they were young with an otherwise low background CVD risk when they were studied by Caplan et al, but not among ARIC participants when they are older with an elevated background CVD risk profile, as in the present study. However, our analyses stratified by median age at CVD event (i.e., 77 years) failed to reach statistical significance.…”
Section: Discussionmentioning
confidence: 50%
“…An earlier study by Caplan et al in a different study population found that among those ≤40 years old, endodontic lesions were significantly associated with incident CHD ( p < 0.05) but found no association among those >40 years old . Other research on infection and CVD has found that infection is a stronger CVD risk factor among those with low background CVD risk compared to those with elevated background CVD risk . It is possible EI was a risk factor for CVD among ARIC participants when they were young with an otherwise low background CVD risk when they were studied by Caplan et al, but not among ARIC participants when they are older with an elevated background CVD risk profile, as in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…Case periods were selected to address the timing and duration of VTE risk after infection similar to study methodology used by Cowan et al 26 and Elkind et al 27 We employed two exposure classification schemes. First, exposure was dichotomized as hospitalization with infection or no hospitalization with infection (referent) which includes participants not hospitalized and those with hospitalizations that did not include an infection.…”
Section: Methodsmentioning
confidence: 99%